Pengaruh Terapi Seni Mewarnai Sketsa Gambar Terhadap Tingkat Kecemasan Anak Usia Prasekolah (3-6 Tahun) Dalam Menjalani Hospitalisasi Di Murni Teguh Memorial Hospital - Zalukhu, Sepriani; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2024)
Hospitalization is a condition where a person is in a situation that requires medical treatment in a hospital to relieve diseases or conditions that often occur in adults and children, hospitalization often occurs in children due to several impacts, one of which is anxiety. Anxiety is an excessive feeling or emotional response to a condition of fear, anxiety, worry that is felt by children. Art therapy is a picture coloring activity that gives children the opportunity to express themselves freely so that they can distract children from anxiety due to pain. This study used a pre experimental design and used the Pre test – Post Test Design method. Sampling using purposive sampling with a total sample of 28 respondents. The research instrument used was an anxiety questionnaire. Analysis of the data used is the Wilcoxon test. The results showed that there was an effect of art therapy coloring sketches on the anxiety level of preschool children (3-6 years) in undergoing hospitalization at Murni Teguh Memorial Hospital Medan, the Wilcoxon statistical test results showed p value < 0.05 (p value = 0.000). It is concluded that there is an effect of art therapy coloring sketches on the level of anxiety of preschool children (3-6 years) in undergoing hospitalization at Murni Teguh Memorial Hospital Medan.